MATHEMATICS EDUCATION STUDENT’S REPRENTATION IN SOLVING ALGEBRA PROBLEMS BASED ON THEIR VARIOUS SPATIAL ABILITY - Baiduri Baiduri (Sriwijaya University Learning and Education International Conference, 2018)
This paper aims to explore and describe the representation made by students of mathematics education in solving algebraic problems based on various spatial abilities. Two students from each of the high, moderate, and low spatial abilities were chosen to be the subject of the study. Data was obtained through in-depth interviews and written answers in answering algebraic problems. The credibility of the data was obtained through continuous observation and source triangulation. The data obtained were analyzed using a flow chart consisting of three activities that occurred simultaneously, namely data reduction, data presentation, and conclusion drawing. The analysis showed that the internal representation of subjects with various spatial abilities differed in understanding the problem and making a solution plan, both questions investigation and finding. The external representation of subjects with various spatial abilities is the same in understanding the problem of inquiry. As for the problem of finding high and low spatial-capable subjects presenting the same external representation. There are similarities in external representations for solving investigation questions between high and low spatial abilities, and between moderate and low spatial abilities for finding problems.